2018
DOI: 10.1111/ajsp.12333
|View full text |Cite
|
Sign up to set email alerts
|

“Narratives of our past:” Taking a journey through history for collective well‐being

Abstract: Past research on life satisfaction is examined mostly at the individual level and with attention to the influence of demographics, personality, and intergroup factors. There has been little, if any, research on how historical narratives affect subjective satisfaction. The current study interviewed a national sample of 1,516 Singapore citizens on how they perceive the history of Singapore. The results identified three distinct narratives that can be broadly themed as Nation-Building, Conflicts and Contestations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…The association between historical narratives and subjective well-being has since been empirically demonstrated in samples from Singapore (Ho et al, 2018), Estonia (Kus, Ward, & Liu, 2013), and the United States (Adler & Poulin, 2009). In their Singaporean sample, Ho et al (2018) found that historical events associated with a strong identification of Singaporean identity had a positive link to subjective well-being (presumably because they reinforced feelings of belongingness and pride), while those associated with questions about Singapore's future survivability had a negative link to subjective well-being. This finding suggests that the type of historical narrative can either positively or negatively predict subjective well-being.…”
Section: Historical Narratives and Well-beingmentioning
confidence: 99%
See 3 more Smart Citations
“…The association between historical narratives and subjective well-being has since been empirically demonstrated in samples from Singapore (Ho et al, 2018), Estonia (Kus, Ward, & Liu, 2013), and the United States (Adler & Poulin, 2009). In their Singaporean sample, Ho et al (2018) found that historical events associated with a strong identification of Singaporean identity had a positive link to subjective well-being (presumably because they reinforced feelings of belongingness and pride), while those associated with questions about Singapore's future survivability had a negative link to subjective well-being. This finding suggests that the type of historical narrative can either positively or negatively predict subjective well-being.…”
Section: Historical Narratives and Well-beingmentioning
confidence: 99%
“…With the exception of Ho et al (2018), no study has been conducted on life satisfaction and history in the context of a developed Asian country like Singapore. Given how the generational character affects collective remembering, this exploratory study thus attempts to (a) explore intergenerational differences in collective remembering, and (b) examine whether intergenerational differences in collective remembering predict well-being.…”
Section: Historical Narratives and Well-beingmentioning
confidence: 99%
See 2 more Smart Citations
“…We do not aim to review or summarize this vast body of literature but suggest that social psychologists can also contribute to this area of inquiry. For example, the social representations of history approach (Liu and Hilton, 2005) suggests that people’s collective representations of local and international histories influence local social identities and intergroup processes and relations (Hakim et al, 2015) and collective well-being (Ho et al, 2018). It is very likely that how people in these postcolonial societies represent facets of their colonial history would be associated with various social psychological processes related to their former colonizers (see e.g., Liu et al, 2002).…”
Section: Introductionmentioning
confidence: 99%